Blood Splats and Bodily Collapse: Reported Realism and the Perception of Violence in Combat Films and Video Games - Bender, Stuart (Berghahn Journals, 2014)
A clear definition of realism is understandably difficult for critics and theorists to agree upon when applied to texts such as the war film or combat shooter, which can have a very direct connection to events that have actually taken place. In this paper, I use textual observation and analysis to advance the concept of “reported realism” as an alternate analytic tool to account for the impression of truth and authenticity produced by specific stylistic components of these representations of combat violence. Drawing upon cognitivist theories of meaning and the imagination (Torben Grodal, Stephen Prince) and neoformalist film studies (Kristin Thompson) this paper points toward some of the significant developments in the evolution of violence in war films as well as the adjacent genre of the first-person shooter video game. I show that the intensified audio-visual detail in contemporary screen representations of war enable film viewers and game players to construct more vividly imagined mental simulations, thus offering a greater affective realism.